A randomized study comparing rectally administered misoprostol after spinal anesthesia versus intramuscular oxytocin for prevention of postpartum hemorrhage in caesarean section - Alwani, Madhuri; Singh, Swapnil; Thakur, Ratna; Mishra, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Post-Partum Hemorrhage (PPH) is the commonest cause of maternal death worldwide. Studies suggest that the use of Misoprostol may be beneficial in clinical settings where oxytocin is unavailable. However studies are limited that show its use in prevention of PPH in high risk pregnancy involving elective caesarean section. Therefore our aim of study is to compare the effectiveness of rectal misoprostol with intramuscular oxytocin in the prevention of postpartum hemorrhage in cesarean sections. Methods: In a double-blind randomized controlled trial, 200 pregnant women who had cesarean sections were assigned into two groups: to receive either oxytocin intramuscularly or misoprostol rectally after spinal anesthesia. Results: There was no significant difference between the two groups about change in postpartum hemoglobin, need for blood transfusion and incidence of PPH. We also did not observe any significant difference in any side effects. Conclusions: Misoprostol may be considered as an alternative for oxytocin in low resource clinical settings.